2022
DOI: 10.1038/s41598-022-17397-4
|View full text |Cite
|
Sign up to set email alerts
|

Managed pollination is a much better way of increasing productivity and essential oil content of dill seeds crop

Abstract: Dill seeds (Anethumgraveolens L.) is the most valuable medicinal seed spice crop of Apiaceae. It bears small yellow flowers in the form of umbels. Being a cross-pollinated crop, floral visitors play vital role in pollination and seed sets. Hence, the present study was conducted at the ICAR-National Research Centre on Seed Spices, Ajmer (Rajasthan), India to discover the pollinator’s community, foraging behaviour and abundance of most frequent pollinators and different modes of pollination on seed yield and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The oil extracted from dill seeds was pale yellow with a strong characteristic aroma and pleasant odor, and the yield was 3.50 ± 0.8% (v/w). The yield of DSEO extraction is higher than that of essential oils extracted from dill seeds planted in India, varying between 1.71 and 2.06% …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The oil extracted from dill seeds was pale yellow with a strong characteristic aroma and pleasant odor, and the yield was 3.50 ± 0.8% (v/w). The yield of DSEO extraction is higher than that of essential oils extracted from dill seeds planted in India, varying between 1.71 and 2.06% …”
Section: Resultssupporting
confidence: 89%
“…Emulsion electrospinning is a promising technique for encapsulating essential oils to improve their sustained-release performance . Essential oils from dill seed are the most valuable medicinal seed spice crops in the Apiaceae . Dill is one such annual aromatic herb, belonging to the family Umbelliferae .…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, it is their ability to transmit many plant viruses (Fiallo-Olivé et al 2020). Essential oils (EOs) have been known for insecticidal activity against a large variety of insects, herbivores, and microorganisms, having some attracting pollinators (Argyropoulou et al 2022;Meena et al 2022). Previous studies have shown their contact toxicity and repellency, with additional action as antibacterial, antifungal, antioxidant, insecticidal, antifeedant, fumigant, miticides, oviposition deterrent, nematocidal and growth regulatory (Li et al 2022;Singh and Pandey 2021;Sahu and Singh 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils (EOs) have been known for insecticidal activity against a large variety of insects, herbivores, and microorganisms, and some are active in attracting pollinators (Argyropoulou et al, 2022;Meena et al, 2022). Previous studies have shown their contact toxicity, repellency, pathogenicity, and growth regulation (Li et al, 2022;Singh and Pandey, 2021;Sahu and Singh, 2022).…”
Section: Introductionmentioning
confidence: 99%